2015
DOI: 10.3109/01612840.2015.1021938
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Physical and Mental Healthcare Needs Among Stimulant-using Gay and Bisexual Homeless Men

Abstract: Purpose Homeless gay and bisexual (G/B) men evidence unmet physical and mental healthcare needs. To gain a greater understanding of predictors of unmet physical and mental healthcare needs, the purpose of this cross-sectional study was to understand correlates of baseline self-reported unmet physical and mental healthcare needs among stimulant-using homeless G/B men (N=422, 18-46 years of age). Methods A structured questionnaire was administered at baseline; data were collected from October 2009 to January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Other studies reported that drug dependence is associated with poor dental health and skin complications such as spider telangiectasias, jaundice, pruritus, hyperpigmentation, skin ulceration, and psoriasis [ 8 , 9 ]. The physical, mental, and social health needs of people who use drugs have been documented worldwide [ 6 , 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported that drug dependence is associated with poor dental health and skin complications such as spider telangiectasias, jaundice, pruritus, hyperpigmentation, skin ulceration, and psoriasis [ 8 , 9 ]. The physical, mental, and social health needs of people who use drugs have been documented worldwide [ 6 , 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Having a sense of psychological connectedness to and participation in the LGBT community has been positively associated with service use (Flores et al, 2017; Frost & Meyer, 2012) and individuals utilize LGBT community centers for counseling or support groups to manage stress related to SGM identities (Frost et al, 2016; Meyer, 2003; Toomey et al, 2018). Increased social support from friends and family has been associated with decreased service use among gay and bisexual men (Coleman et al, 2017; Salem et al, 2015) and SGM peers have been shown to provide more support for emotional distress to youth than parents and non-SGM peers (Doty et al, 2010). Religious affiliation was found to be both a source of support and a stressor.…”
Section: Social Identity and Mental Health Service Usementioning
confidence: 99%
“…In addition to a lack of understanding about the pathways to homelessness among SGM adults, the current literature tends to focus on HIV or substance use, 8,9 with little information about the ways in which the lived experiences of SGM adults experiencing homelessness may differ from their non-SGM counterparts. The sampling methods used in previous studies are similarly limited with the majority sampling homeless individuals from within SGM communities.…”
Section: Introductionmentioning
confidence: 99%